1997
DOI: 10.1055/s-2007-972645
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combined Endurance, Strength and Sprint Training on Maximal Oxygen Uptake, Isometric Strength and Sprint Performance in Female Elite Handball Players During a Season

Abstract: Eight female handball players from the Norwegian national team were tested for maximal oxygen uptake, maximal isometric strength and maximal running velocity on four occasions during a year. The first test (T1) was made at the beginning of the preparation for a new season, the second (T2) in the middle of the preparation period, the third (T3) at the beginning of the season for the national league, and the fourth (T4) just before the most important tournament for the national team that year. Between T1 and T2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 1 publication
(1 reference statement)
4
23
0
4
Order By: Relevance
“…This differences especially VO 2 explained that the training effects occurred. Jensen et al (1997) found that VO 2 max values of Norwegian women handball players in pre-training had 51.3 ± 2.3 ml.kg.min -1 and post-training 53.8 ± 2.7 ml.kg.min -1 but the present study has showed that VO 2 max values of Turkish women handball players in pre-training was 49.0-49.1 ml.kg.min -1 and in post-training was 50.5-51.5 ml.kg.min -1 . Although VO 2 max values in Jensen et al (1997) have been higher than the present study, there are similar increases in these two studies as training effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This differences especially VO 2 explained that the training effects occurred. Jensen et al (1997) found that VO 2 max values of Norwegian women handball players in pre-training had 51.3 ± 2.3 ml.kg.min -1 and post-training 53.8 ± 2.7 ml.kg.min -1 but the present study has showed that VO 2 max values of Turkish women handball players in pre-training was 49.0-49.1 ml.kg.min -1 and in post-training was 50.5-51.5 ml.kg.min -1 . Although VO 2 max values in Jensen et al (1997) have been higher than the present study, there are similar increases in these two studies as training effects.…”
Section: Discussionmentioning
confidence: 99%
“…Горостиага и сарадници (Gorostiaga, Granados, Ibanez, Gonzalez-Badillo, & Izquierdo, 2006) су открили значајне везе између излазне мишић-не снаге горњих и доњих телесних екстремитета која је повезана са тренингом снаге и тренинга издржљивости високог интезитета током читаве тренажне сезоне код врхунских рукометаша. Ис-питивање утицаја тренинга би могло да буде од великог значаја за оптималну израду физичких и спортом одређених програма условљавања ради побољшања перформанси у рукомету (Jensen et al, 1997). Ако су физичко условљавање, техничке и тактичке вежбе у рукомету довољно добри да обезбеде адекватне стимулансе, нарочито за по-бољшање мишићне снаге, физичке перформансе рукометашица се могу унапредити.…”
Section: уводunclassified
See 1 more Smart Citation
“…O tempo gasto em esforços de baixa intensidade é proporcionalmente maior do que nos esforços de alta intensidade (3) , ou seja, relacionado ao condicionamento físico necessário e determinante da modalidade, atletas de alto nível de rendimento devem estar em condições de intervir muitas vezes na partida, com ações rápidas e potentes como saltar, bloquear, realizar sprints e arremessar (4)(5)(6)(7)(8) , bem como condicionamento específico de resistência (9) . Deste modo, para atingir esse nível de condicionamento é importante a sistematização e o controle das cargas de treinamento, bem como dos períodos de recuperação, levando em consideração os objetivos específicos e as características básicas de cada atleta (10) .…”
Section: Introductionunclassified
“…Embora exista uma vasta literatura internacional que objetivou contemplar diversos aspectos do handebol como força máxima (6) e explosiva (6,7) , consumo máximo de oxigênio (8,9) , e capacidade aeróbia (6,7,9) , em nível nacional, muito pouco tem sido realizado para caracterização fisiológica dos atletas dessa modalidade esportiva.…”
Section: Introductionunclassified